Filamentous Hemagglutinin of Bordetella pertussis Does Not Interact with the β2 Integrin CD11b/CD18 - Golshani, Maryam; Rahman, Waheed Ur; Osickova, Adriana; Holubova, Jana; Lora, Jinery; Balashova, Nataliya; Sebo, Peter; Osicka, Radim (International journal of molecular sciences, 2022)
The pertussis agent Bordetella pertussis produces a number of virulence factors, of which the filamentous hemagglutinin (FhaB) plays a role in B. pertussis adhesion to epithelial and phagocytic cells. Moreover, FhaB was recently found to play a crucial role in nasal cavity infection and B. pertussis transmission to new hosts. The 367 kDa FhaB protein translocates through an FhaC pore to the outer bacterial surface and is eventually processed to a ~220 kDa N-terminal FHA fragment by the SphB1 protease. A fraction of the mature FHA then remains associated with bacterial cell surface, while most of FHA is shed into the bacterial environment. Previously reported indirect evidence suggested that FHA, or its precursor FhaB, may bind the β2 integrin CD11b/CD18 of human macrophages. Therefore, we assessed FHA binding to various cells producing or lacking the integrin and show that purified mature FHA does not bind CD11b/CD18. Further results then revealed that the adhesion of B. pertussis to cells does not involve an interaction between the bacterial surface-associated FhaB and/or mature FHA and the β2 integrin CD11b/CD18. In contrast, FHA binding was strongly inhibited at micromolar concentrations of heparin, corroborating that the cell binding of FHA is ruled by the interaction of its heparin-binding domain with sulfated glycosaminoglycans on the cell surface.
Keywords: antigeny CD18; Humans; filamentous hemagglutinin; Peptide Hydrolases; Integrins; makrofágový antigen 1; faktory virulence rodu Bordetella; glykosaminoglykany; hemaglutininy; lidé; Hemagglutinins; Bordetella pertussis; bakteriální adheziny; heparin; Bacterial Adhesion; integrin; pertuse; Macrophage-1 Antigen; CD11b/CD18; Glycosaminoglycans; Heparin; bakteriální adheze; integriny; Adhesins, Bacterial; Whooping Cough; CD18 Antigens; Virulence Factors, Bordetella; proteasy; adenylate cyclase toxin